2016
DOI: 10.1007/s10661-016-5692-6
|View full text |Cite
|
Sign up to set email alerts
|

Potable water quality monitoring of primary schools in Magura district, Bangladesh: children’s health risk assessment

Abstract: Safe potable water is essential for good health. Worldwide, school-aged children especially in the developing countries are suffering from various water-borne diseases. In the study, drinking water supplies for primary school children were monitored at Magura district, Bangladesh, to ensure safe potable water. APHA standard analytical methods were applied for determining the physicochemical parameters of the water samples. For determination of the essential physicochemical parameters, the samples were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
1
24
2
Order By: Relevance
“…These factors contribute to the microbial growth and to considerable changes in the concentration and composition of the water (Proctor & Hammes, 2015). These results were similar to those found in other studies, which have also analyzed the water in school settings (Marzano & Balzaretti, 2013;Rahman et al, 2016) and revealed the need to reevaluate the quality of this resource.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…These factors contribute to the microbial growth and to considerable changes in the concentration and composition of the water (Proctor & Hammes, 2015). These results were similar to those found in other studies, which have also analyzed the water in school settings (Marzano & Balzaretti, 2013;Rahman et al, 2016) and revealed the need to reevaluate the quality of this resource.…”
Section: Resultssupporting
confidence: 88%
“…In schools, water is used to be thirst-quenching, to prepare food and to use in personal hygiene. If drinking water is not safe, this supply can transport pathogenic microorganisms, which represents a health risk for students, teachers, and staff (Rahman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractures within the river system may lead to mineralized regimes that produce mineral veins and saline intrusion into the river which in turn result in elevated major ions in the river water. Studies have shown that high intake of sodium in drinking water may lead to hypertension in pregnant women (Alsulaili et al 2015), and children whose kidneys are not mature enough to excrete excess sodium (Rahman et al 2016). Infants with severe gastrointestinal infections can suffer from fluid loss, leading to dehydration and increased sodium levels in the plasma (hypernatraemia) and serious neurological damage occasioned by high intake of sodium (Rahman et al 2016;Scheelbeek et al 2016).…”
Section: Major Cationsmentioning
confidence: 99%
“…The level of heavy metals in the tube well water samples were as follows: As from 1 to 55 µg/L, Fe from 40 to 9890 µg/L, and Mn from 10 to 370 µg/L. Drinking water parameters of Magura district did not meet the requirement of the World Health Organization drinking water quality guideline, or the Drinking Water Quality Standards of Bangladesh [6].…”
Section: Introductionmentioning
confidence: 98%